ANALYSIS MATRICE OPERATION EXPRESSION WITH FACIAL CHARACTER ON CONTROLLER POSITION - Sonia All Risqi (Politeknik Negeri Batam, 2019)
Creating expressive 3D facial animation characters and and being able to visualize the character's facial expression becomes realistic is a challenge topic for the animator. Facial expression animation is an important aspect in 3D environments to create the presence of characters, determine emotions, help convey messages, and make animations more alive. The problem that arises is that it takes a long time in the process of work and the complexity of the various movements. But this should still be done well so that the virtual characters can display a natural expression. Controller techniques are used to perform the formation of facial expressions of 3D characters are visualized based on facial expressions so that the desired character message message can be conveyed and help speed up the process of making character facial movement. The controller position of x, y and z in this final project is an expression matrix operation of animation. This research uses character model and asset on a free rig 3D animation character as sample test. Test method used is the validity and reliability of the results of the questionnaire submitted to the 3D animator experts. The result of this research is the matrix database in the form of movement model of facial expressions, sad, angry, fear and shocked 3D characters that can be integrated on other character character models that have similar number of controller characteristics, this database will shorten the process of 3D character facial movement.